2016
DOI: 10.1016/j.str.2015.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling Catalytic and Binding Functions in the Cyclic AMP-Dependent Protein Kinase A

Abstract: SUMMARY The canonical function of kinases is to transfer a phosphoryl group to substrates, initiating a signaling cascade; while their non-canonical role is to bind other kinases or substrates, acting as scaffolds, competitors, and signal integrators. Here, we show how to uncouple kinases dual function by tuning the binding cooperativity between nucleotide (or inhibitors) and substrate allosterically. We demonstrate this new concept for the C-subunit of protein kinase A (PKA-C). Using thermocalorimetry and NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 71 publications
7
35
0
Order By: Relevance
“…Furthermore, R133A exhibited a nearly 200-fold higher IC 50 value for inhibition by PKI (Supplementary Figure S4), confirming loss of enzyme inhibition despite unchanged autophosphorylation and ATP affinity. Interestingly, the binding of both PKI (pseudosubstrate inhibitor) and ATP/Mg (nucleotide) to the WT C-subunit was additive, or even synergistic, over a range of ATP concentrations (Figure 4B), confirming that DSF detects co-operative binding at two separate sites on PKAc, consistent with recent work [41].
Figure 4.PKI protein binds stably to PKAc WT, but not K72H or R133A protein.( A ) Native ESI mass spectra of PKAc WT, K72H and R133A, in the absence or presence of equimolar PKI.
…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, R133A exhibited a nearly 200-fold higher IC 50 value for inhibition by PKI (Supplementary Figure S4), confirming loss of enzyme inhibition despite unchanged autophosphorylation and ATP affinity. Interestingly, the binding of both PKI (pseudosubstrate inhibitor) and ATP/Mg (nucleotide) to the WT C-subunit was additive, or even synergistic, over a range of ATP concentrations (Figure 4B), confirming that DSF detects co-operative binding at two separate sites on PKAc, consistent with recent work [41].
Figure 4.PKI protein binds stably to PKAc WT, but not K72H or R133A protein.( A ) Native ESI mass spectra of PKAc WT, K72H and R133A, in the absence or presence of equimolar PKI.
…”
Section: Resultssupporting
confidence: 89%
“…Moreover, different C- and R-subunits can co-assemble to generate distinct quaternary complexes, although their composition and stoichiometry are potentially susceptible to artifacts of crystallization. Importantly, intrinsic co-operativity within the C-subunit exists [40], so that ligand binding is sensed conformationally, potentially coupling ATP site occupancy with substrate dynamics during the catalytic cycle [41]. Classes of small-molecule or protein ligands might therefore exhibit differential effects on PKA signaling, potentially through distinct binding modes, as noted for several kinase and inhibitor combinations [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…A clear extension from this work will be to explore whether the mechanisms identified here are observed for other AGC kinases as well as non-AGC kinases. For example, in agreement with previous studies, we observed that both PKC and PKA show positive cooperativity between substrate and ATP binding (43). We posit that it is likely not a universal kinase mechanism as a recent paper (44) found that negative cooperativity is observed in the tyrosine kinases Src, Abl, and Hck.…”
Section: Journal Of Biological Chemistry 21967supporting
confidence: 92%
“…An interesting functional aspect observed in some kinases is substrate binding cooperativity. Experimental studies of the cyclic AMP-dependent PK (PKA), considered to be a prototypical member of the kinase family, indicate that binding first the ATP increases the affinity toward the protein substrate (11)(12)(13). A puzzling fact is that a single point mutation of tyrosine 204, which does not form interactions with any of the substrates, to alanine (Y204A) decouples ligand binding to the catalytic subunit but does not alter its crystal structure (11,14).…”
mentioning
confidence: 99%